Cultural influences on infant and toddler feeding among low‐income Latinx mothers - Alexandra L. MacMillan Uribe; Hannah G. Rudt; Tashara M. Leak (Wiley, 2022)
Abstract Latinx infants and toddlers experience higher obesity rates than their black or white counterparts, increasing chronic disease risk later in life. Infant and toddler feeding (ITF) interventions are shown to improve dietary behaviours, but few studies target Latinx populations. Culturally tailoring such interventions is imperative, but cultural influences on Latinx ITF practices remain unclear. The purpose of this study was to characterize how culture influences ITF practices among Latinx mothers of low income. A brief survey and semistructured interview informed by the theory of planned behaviour (TPB) were conducted on Zoom with New York City‐based Latinx mothers of children 4 to 24 months old. A directed content analysis approach was used to identify themes using TPB theoretical codes and inductive codes. Transcripts were coded independently by two researchers using NVivo 12. Survey data were analyzed using descriptive statistics in Excel. Participants (n = 19) were of Dominican, Mexican and Central and South American origin, had low acculturation scores and mean child age was 16.7 months (range: 5-24 months old). The central theme identified was that participants balanced cultural information with evidence‐based health information to determine which ITF practices were most beneficial to infant/toddler health. This resulted in the adoption of evidence‐based ITF recommendations, adoption of cultural practices that aligned with evidence‐based recommendations and dismissal or postponement of cultural ITF practices that contradicted evidence‐based recommendations. The present results can be applied to culturally relevant ITF education as follows: emphasizing the benefits of desirable ITF practices on children's health and promoting healthy cultural ITF practices.